Mobile Commerce Adoption : Literature Review Of Factors Affecting It (Trinity Journal of Management, IT & Media (TJMITM), 2016)
With the emergence of high-end mobile devices and advanced  internet technologies (such as 3G and 4G) mobile commerce  market has become an attractive and profitable arena for  businesses and marketers. The latest buzz in the industry is the  transition from wired to wireless networks, i.e. from electronic  commerce to mobile commerce or m-commerce. However, mobile  commerce is still in its initial stages in terms of its adoption by  the end users. The purpose of this study is to identify important  factors having significant role in determining mobile commerce  adoption intention by consumers and to propose a model utilising  the identified factors. For this, a thorough review of literature  available on mobile as well as adoption of similar technologies  was done. An in-depth study of factors influencing consumers’  decision about mobile commerce can provide useful insights  to the concerned marketers for developing suitable marketing  strategies.
Keywords: Mobile commerce; Adoption; Marketing strategies